Relationship of Eating Behavior, Knowledge, Attitudes, Physical Activities, and Parent Support with Obesity Events in Adolescents in Padang City - Deswita, Deswita; Lipoeto, Nurindrawaty; Mudjiran, Mudjiran; Abdullah, Khatijah Binti (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: A report from the West Sumatra Provincial Health Office in December 2017 showed increase in the percentage of overweight and obese children in the city of Padang. In 2014, overweight children amounted to 4.86% and an increase in 2016 to 6.44%. AIM: This study aimed to determine the most dominant risk factors affecting the incidence of obesity in adolescents in Padang City. MATERIALS AND METHODS: This study was conducted on 484 respondents from 4 (four) schools, namely SMPN 26, SMPIT Adzkia, SMAN 3, and SMA Adabiah Padang in December 2019-February 2020. Data analysis used the Chi-square test and multiple logistic regression tests. RESULTS: The multivariate analysis results showed that adolescents’ eating behavior variable was the most dominant factor affecting adolescents’ incidence of obesity with a significance value of p < 0.05 and Exp (B) 14.11. These results showed that adolescents who behave eat poorly at 14.11 times, have the risk of obesity more than adolescents who eat well. CONCLUSIONS: Adolescent eating behavior variables can predict the incidence of obesity in adolescents together with adolescent physical activity variables, adolescent attitudes, and adolescent knowledge.